The Effectiveness of the Project Citizen Learning Model on Student’ Critical Thingking Skills on the Topic of Preserving My Nation's Cultur (A Quasi-Experimental Study in Eighth Grade at SMP Negeri 3 Purbalingga) - Amalia Fitriani; Efi Miftah Faridli; Eko Priyanto (UM Purwokerto Press, 2024)
This study aims to determine the impact of applying the Project Citizen learning model on students' critical thinking skills in the Pancasila Education subject for Grade VIII at SMP Negeri 3 Purbalingga. The method used in this study is quasi-experimental with a nonequivalent control group design. The sample consists of 32 students from class VIII F as the experimental group and 32 from class VIII G as the control group. Data collection techniques included questionnaires, observation, and documentation. Based on statistical analysis using SPSS, a significance value of 0.000 0.05 was obtained, indicating that the null hypothesis (HO) is rejected and the alternative hypothesis (HA) is accepted. The percentage results showed an increase in the experimental group's performance from 71% before the intervention to 81% after the intervention, resulting in a 10% improvement. It can be concluded that the Project Citizen learning model significantly impacts the critical thinking skills of Grade VIII students at SMP Negeri 3 Purbalingga on the topic of preserving my nation's culture.